Ant Colony Optimization (ACO) in Disaster Information Network - Mr. A. V. Zade; Dr. R. M. Tugnayat (International Journal of Innovations in Engineering Research and Technology, 2021)
Swarm intelligence is a relatively new approach to problem solving that takes inspiration from the social behaviors of insects and of other animals. In particular, ants have inspired a number of methods and techniques among which the most studied and the most successful is the general purpose optimization technique known as ant colony optimization. The goal of this article is to introduce ant colony optimization and to survey its most notable applications. A better understanding of the theoretical properties of ACO algorithm is certainly another research direction that will be pursued in the future